2007
DOI: 10.1007/s00436-007-0708-3
|View full text |Cite
|
Sign up to set email alerts
|

Cestode parasitism in invasive and native brine shrimps (Artemia spp.) as a possible factor promoting the rapid invasion of A. franciscana in the Mediterranean region

Abstract: Artemia franciscana is an invasive crustacean expanding its range in hypersaline wetlands in the Mediterranean region and replacing native Artemia parthenogenetica and Artemia salina. Native brine shrimps are known as intermediate hosts of cestodes; infected individuals exhibit changes in their behaviour and appearance, thus facilitating the parasite transmission to the avian hosts by predation. To assess whether invasive brine shrimps participate in the cestode life cycles to the same extent as the native spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
56
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 37 publications
2
56
0
Order By: Relevance
“…Even if at first sight males seem to be more infected than females, probably because of the sexratio (2.79) being in favour of males in this period (Amarouayache et al 2004), statistical data showed no significant differences between the two sexes. Georgiev et al (2007) brought back the same conclusions for Iberian Artemia populations. Parasitic intensity is low in Algerian populations (less than 3 cysticercoids per individual).…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Even if at first sight males seem to be more infected than females, probably because of the sexratio (2.79) being in favour of males in this period (Amarouayache et al 2004), statistical data showed no significant differences between the two sexes. Georgiev et al (2007) brought back the same conclusions for Iberian Artemia populations. Parasitic intensity is low in Algerian populations (less than 3 cysticercoids per individual).…”
Section: Discussionsupporting
confidence: 62%
“…The latter authors studied the distribution of the parasites in various populations of Artemia from the French salterns and highlighted the role of brine shrimp as intermediate host of cestodes parasitizing flamingos. Amat et al (1991a, b), Varó et al (2000), Georgiev et al (2005Georgiev et al ( , 2007 and Sánchez et al (2006Sánchez et al ( , 2007Sánchez et al ( , 2009) studied cestode parasitism in Spanish Artemia populations and their effect on the behaviour of the intermediate host.…”
Section: Introductionmentioning
confidence: 99%
“…Native brine shrimps in the Mediterranean are intermediate hosts of 12 species of avian cestodes parasitic as adults in flamingos, gulls, grebes, shorebirds or ducks (Gabrion et al 1982;Thiéry et al 1990;Robert and Gabrion 1991;Amat et al 1991b;Mura 1995;Georgiev et al 2005Georgiev et al , 2007Vasileva et al 2009;Amarouayache et al 2009). Both adult shrimps and metanauplii participate in cestode life cycles (Redón et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…as the main macroinvertebrate (Sánchez, Green & Castellanos, 2006). However, a diverse community of waterbirds preying on the shrimps maintains up to 15 species of cestodes within the Artemia population, each using a specific waterbird group as final hosts (Georgiev et al, 2005(Georgiev et al, , 2007. Thus, these cestodes constitute an important fraction of the total invertebrate diversity in these systems.…”
Section: Supporting and Regulating Services (1) Biodiversity Of Omentioning
confidence: 99%